On Logarithmically Asymptotically Optimal Hypothesis Testing of Three Distributions for Pair of Independent Objects - Haroutunian, Evgueni A.; Hakobyan, Parandzem (Mathematical Problems of Computer Science, 2021)
The problem of hypotheses testing for a model consisting from two independent objects is considered. It is supposed that three probability distributions are known and objects independently from each other follow to one of them. The matrix of asymptotic interdependencies (reliability{reliability functions) of all possible pairs of the error probability exponents (reliabilities) in optimal testing for this model is studied. The case with two independent objects and two given probability distributions was elaborated by Haroutunian and Ahlswede.